The Influence of Programme of Study in the Use of Library By Undergraduate Students in Nigeria - Oyedum, Georgina Uchey (Ghana Library Journal, 2013)
Adequate use of university libraries is essential for students offering different programmes in order to achieve their academic pursuits. This paper, therefore, assessed the extent to which the programme of study influences the undergraduate students’ use of Federal University libraries in Nigeria. The study also investigated which of the programmes of study influences the students’ use of university libraries most. The survey research method was used for the study and the study population was 1,453 undergraduate students from across Arts, Education, Engineering, Law, Science and Social Science faculties in the selected universities. The main instrument used for the data collection was a questionnaire. Descriptive statistics such as frequency and percentage tabulation were used in analyzing the data. Results revealed that the influence of  programme of study on students’ use of Federal University libraries in Nigeria is low. The study also revealed that students from the social science related disciplines use the university libraries most in Nigeria. To increase the level of library use by the undergraduate students in Federal Universities in Nigeria, majority of the respondents indicated the need for provision of sufficient library collections. Others indicated provision of library Internet connected computers and provision of sufficient and current library collections that would satisfy the information needs of the users.